Philcarneum new genus and Constricticollis new genus, two distinctive rhinoceros beetles (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) from opposite sides of Australia with a revised key to the Australian dynastine genera - Allsopp, Peter G.; Hutchinson, Paul M. (Zootaxa, 2023)
Females of two unusual dynastines (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) from Australia are described and compared with other known Australian genera and species. Philcarneum aenigma Allsopp & Hutchinson new genus, new species from coastal southeastern New South Wales was recognised as novel in the 1980s, but has lacked a formal name, making it ‘invisible’ in the literature. It is placed in the Cheiroplatina. Constricticollis clunis Hutchinson & Allsopp new genus, new species recently captured near Kununurra, northern Western Australia is placed in the Pentodontina. Within the Dynastinae many important generic-level characters relate to mouthpart morphology, which are not sexually dimorphic, thus allowing to determine females to genera in absence of males, whose secondary sexual characters (obvious horns, claw modifications, antennal club length, etc.) are often used in keys. The key to Australian Dynastinae in Weir et al. (2019) is modified to accommodate these two genera and Erbmahcedius Hutchinson & Allsopp, 2021. Distributional maps and data on habitats are provided.